Implementation Science of Paediatric Palliative Care in Lower-Middle-Income Countries in Southeast Asia: An Integrative Review. - Maniago, Jestoni D.; Ngaya-an, Floreliz V. (Indian Journal of Palliative Care)
There is an ongoing development in the paediatric palliative care (PPC) program in Southeast Asia (SEA). However, the implementation process has not been clearly understood among lower-middle-income countries (LMICs) in this region. The purpose of this paper is to review and synthesise research about the implementation process of 7 identified LMICs in the SEA: Cambodia, Indonesia, Myanmar, Lao PDR, the Philippines, Timor-Leste, and Vietnam. An integrative review utilising Whittemore and Knafi's five-stage process was employed. Electronic searches of CINAHL, Web of Science, ProQuest, and Google Scholar (no year restriction) were conducted. From the 7599 articles retrieved, only 11 met the eligibility criteria. Each article was appraised for methodological quality (QualSyst tool and AACODS checklist) and constant comparison methods were used. Two overarching themes emerged in this review - the gaps in PPC standards, practice framework, and guidelines and the PPC challenges and implementation strategies. Understanding the implementation science of PPC among LMICs in the SEA region addresses the gap between idealism and realism. It provides reliable information in the development of strategic work plans that will improve the implementation process and promote the translation of EBIs into practice significant to the quality of paediatric patient outcomes.